Evidance Based Intervensi Psikologi Terhadap peningkatan strategi DOTS Pada Pasien Tuberkulosis: A Systematic Review - Gevi Melliya Sari; Bernadetta Germia Aridamayanti; Sariati Sariati; Dwi Uswatun Sholikhah; Cahya Mustika Narendri; Wimar Anugrah Romadhon (FORIKES, 2020)
Background: Psychological problems are one of the factors that influence tuberculosis patient compliance. Psychological intervention is needed to help patients cope with stressors experienced during the treatment period of at least 6 months and increase patient compliance in undergoing treatment. Objective: To outline some of the benefits of psychological interventions that can help pulmonary tuberculosis patients follow treatment. Method: The database used in this study is Scopus, Google Scholar, and Pubmed is limited to the last 5 years of publication from 2016 to 2020, full-text article in English. The keywords used are